Regiocontrolled Annellation Reactions Starting from Diethoxymethyl Protected Indole - Gmeiner, Peter; et al. (Synthesis-Stuttgart, 2000)
Directed metallation of the diethoxymethyl protected indole 4 followed by treatment with β-nitrostyrene leads to the 1,2- disubstituted indole 5. Using 5 as a central intermediate, the tricyclic annellation products of type 2 and 3 were accessed when the regiochemical outcome of the reactions could be controlled.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.lphch.regioc
Keywords: Indoles; Metallation; Rearrangements